Incorporating peer tutoring for reading activity in the Malaysian school setting : A review of literature - Nirmala, D/O Muniandy (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The purpose of this project paper is to high it the usefulnesosf peer tutoring in the teaching of reading activity in Malaysian school setting and the benefits that peer tutoring will bring to the tutor, tutee and the teachers who are involved in this scheme. Suggestions are given on how to incorporate peer tutoring for reading activity in Malaysia school setting. Various peer tutoring schemes have been implemented over the years in America, United Kingdom and Australia by using childu+en, college and university students as tutors. Some of the schemes prove to be successful. Various research findings have been put forward as an evidence that poor tutoring is a useful technique that should not be overcook. The findings of the peer tutoring schemes stated in this project paper were very encouraging. Students who are involved in pax tutoring go through changes from the behavioral perspective, attitudes towards the subject matter, increased motivation and increased fluency in reading. An example of lesson plan is provided to highlight peer tutoring as a useful technique that can be easily adapted into the teaching of reading in the classroom.